2000
DOI: 10.1271/bbb.64.1096
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids in Human Blood Plasma after Ingesting Paprika Juice

Abstract: We investigated the presence of different carotenoids in male human subject after the ingestion of paprika juice, and identified capsanthin, capsanthone, cucurbitaxanthin A, 11-cis-capsanthin, lutein and zeaxanthin in the human plasma. These results suggest that capsanthone and 11-cis-capsanthin might be as important as capsanthin for human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…Therefore, it is possible that capsanthone in plasma was an oxidative metabolite of capsanthin produced in vivo. Similar findings have also been reported by Etho et al 17 . The total plasma carotenoid level was increased 1.2-fold by 2 weeks of carotenoid supplementation from 1907 to 2362 pmol/mL , but the total plasma carotenoid level after 4 weeks of c supplementation was slightly lower than that at 2 weeks.…”
Section: Singlet Oxygen-quenching Activity Of Carotenoidssupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, it is possible that capsanthone in plasma was an oxidative metabolite of capsanthin produced in vivo. Similar findings have also been reported by Etho et al 17 . The total plasma carotenoid level was increased 1.2-fold by 2 weeks of carotenoid supplementation from 1907 to 2362 pmol/mL , but the total plasma carotenoid level after 4 weeks of c supplementation was slightly lower than that at 2 weeks.…”
Section: Singlet Oxygen-quenching Activity Of Carotenoidssupporting
confidence: 92%
“…Capsanthone is found in paprika, but at a very low level less than 0.5 of total carotenoids . Therefore, as reported by Etoh et al 17 , the capsanthone we detected in plasma and erythrocytes was presumably an oxidative product of capsanthin. Recently, several oxidative metabolites of lutein, zeaxanthin, and lycopene have been found in humans and other mammals.…”
Section: Oxidative Metabolite Of Capsanthinsupporting
confidence: 84%
See 1 more Smart Citation
“…The reduction in ox-LDL levels (Figure 2C) and the increase in HDL levels (Figure 2A) after the treatment of diabetic rats with yoghurt-enriched bixin were similar to the lycopene effects. Although the individual treatments with lycopene and bixin promoted similar responses in most of the parameters, the differences in the magnitude of the responses in glycemia and triacylglycerol between these carotenoids (for example, lycopene was better than bixin) can be explained by the fact that polar carotenoids (such as bixin) have a rapid clearance rate from the plasma [31]; hence, if bixin also has a short half-life, this could possibly be the reason why the TBARS levels were not decreased in the plasma of diabetic rats treated with bixin (Figure 2B).…”
Section: Discussionmentioning
confidence: 99%
“…14) Etoh et al identified capsanthone in the plasma of human subjects who had consumed paprika juice. 15) Our results indicate that capsanthin photo-degradation might involve oxidative conversion into analogous colored compounds without chain scission.…”
mentioning
confidence: 69%